To Snore Or Not to Snore - Yawusi, B.N (Pilgrims Books Ltd, 1970)
A death sentence is passed on anyone who snores,when sleeping at night in the village.One of the two travellers passing the night in the village snores.The second traveller,aware that they would be killed,converts the snoring into a dancing tune to the merriment of the villagers.
Keywords: Folktales